Liposomal Encapsulation of Acyclovir: Enhancing Bioavailability, Targeted Delivery, and Therapeutic Efficacy in Herpesvirus Infections - Noor Mustafa Shaker; Zainab Noori Salman (International Journal of Medical Toxicology and Legal Medicine, 2024)
For years, acyclovir has remained the first-choice antiviral agent in the management of herpes viral infections due to its high specificity and excellent tolerability. However, severely low bioavailability, poor cell-type permeability, and lack of selective targeting contribute to significantly compromised therapeutic results. Despite various strategies adopted to overcome these barriers, the ideal oral route remains elusive for acyclovir even today.Liposome-encapsulated acyclovir is a promising, emerging approach for the treatment of herpesvirus infections. As the development of drug formulations necessitates translational assessments, preclinical studies on pharmacokinetics, biodistribution, excretion, and toxicity are essential to analyze the compatibility of the liposomal delivery system. Before liposomal acyclovir can be extensively used as a therapeutic drug, long-term consequences for nontarget cells and systems have to be investigated. Negatively interacting therapeutically useful agents, such as irradiation, with the liposomal delivery system should also be assessed. In all of the presented studies, an additional evaluation after the already mentioned time periods has not been conducted. Yet, liposome-based formulations can remain in certain organs for much longer, as shown for liposomal drugs. As one major cause of liposome retention in tissues is phagocytosis by macrophages, an organ-by-organ evaluation of liposome accumulation in macrophages is mandatory.